Anti-corrosion performance of the conductive bilayer CrC/CrN coated 304SS bipolar plate in acidic environment. (September 2022) - Pan, T.J.; Dai, Y.J.; Jiang, J.; Xiang, J.H.; Yang, Q.Q.; Li, Y.S.
Abstract: A bilayer CrC/CrN coating prepared on 304 stainless steels (304SS) using reactive radio frequency magnetron sputtering technique (RF-MS) is investigated in acidic fuel cell environment. Compared to the CrN monolayer, the synergistic function of bilayer structure effectively hinder penetration of corrosive substance through defects, significantly increases anti-corrosion of substrate. This is attributed to the increased compactness of coating and the good matching between layers to effectively enhance interfacial adhesion. Interfacial contact resistance (ICR) of the CrC/CrN covered 304SS is lower than that of substrate. These effects are closely associated with inherent characteristic and combined preparation method of the coating. Highlights: Gradient CrC/CrN structure improved the matching between layer bonding. Conductivity of coating was better than that of matrix before and after corrosion. Bilayer coating enhanced anti-corrosion and hydrophobicity of substrate. Combined surface technique induced good synergistic effect of bilayer structure.